Digital Democracy, Political Literacy, and Post-Truth Politics: A Systematic Literature Review of Their Influence on Generation Z's Political Engagement - Agust Jovan Latuconsina; Fendy Suhariadi; Suparto Wijoyo (Nusantara: Journal of Law Studies, 2026)
This study addresses the growing challenge of understanding how digital democracy, political literacy, and post-truth politics collectively influence Generation Z’s political engagement in Indonesia amid the rapid expansion of digital media and increasing exposure to misinformation. It seeks to answer the following research questions: (1) How have studies on digital democracy, political literacy, and post-truth politics evolved? (2) What are the dominant research themes and emerging trends in this field? Furthermore, (3) How do these factors shape Generation Z’s political participation in the Indonesian context? To address these questions, this study employs a systematic literature review based on the PRISMA framework combined with bibliometric analysis. A total of 1,382 publications published between 1979 and 2024 were analysed using Biblioshiny in RStudio to identify publication trends, thematic clusters, collaboration networks, and research gaps. The findings reveal that digital democracy has significantly expanded opportunities for Generation Z’s political participation by facilitating access to information, political expression, and civic engagement. However, these opportunities are accompanied by challenges, including the widespread dissemination of misinformation, limited political literacy, and the growing influence of emotional narratives characteristic of post-truth politics. The analysis further emphasises the importance of political literacy and civic education in strengthening young people's ability to evaluate political information and critically resist disinformation. This study contributes to the academic literature by integrating systematic literature review and bibliometric analysis to provide a comprehensive overview of research developments, identify underexplored areas, and propose a conceptual foundation for future studies on youth political engagement in the digital era. Furthermore, the findings offer practical implications for educators, policymakers, and digital platform regulators in designing evidence-based strategies to promote informed, resilient, and democratic political participation among Generation Z in Indonesia.